Artificial intelligence in data storage systems - V. V. Zhilin; O. A. Safar'yan (Advanced Engineering Research)
Introduction. The artificial intelligence (AI) performance in data storage systems is considered. When working with data, the advantage of its use both in economic terms and for security is determined. The work objective is the introduction of artificial intelligence in data storage systems. The key tasks involve the description of methods for data separation, organization of itsstorage and counteraction to security threats.Materials and Methods. The data that should be fed into the drives is divided into parts so that it can be restored without one of the parts. This is necessary to be able to access and recover information in the event of a software or hardware failure.Results. The AI performance under detecting security threats is considered. Since the model implies the interaction of users with data, it was found out how the data access control is carried out and the keys are stored.Discussion and Conclusions. The use of AI in organizing a data warehouse will speed up the system. Artificial intelligence with built-in machine-learning algorithms will provide responding to a situation that affects the state of the sys-tem. Analysis of the state of the drives will avoid a possible hardware or software failure. Minimization of the human factor in the system operation contributes to the improvement of its work.